The United Nations Convention on Contracts for the International Sale of Goods: The Canadian Experience - Sharma, Rajeev (Victoria University of Wellington Law Review, 2005)
The author discusses the Canadian jurisprudence involving the application, or potential application, of the CISG. He concludes that the Canadian courts are beginning to implement the CISG, but that there is still a tendency to apply domestic law alongside, or even in preference to, the international sales law, even when this is not warranted.